ANALISIS KESALAHAN SINTAKSIS PADA ARTIKEL JURNAL ILMIAH MAHASISWA [ANALYSIS OF SYNTAX ERRORS IN STUDENT SCIENTIFIC JOURNAL ARTICLES] - Nababan, Ernie Bertha; Rianto; Kusuma, Dewi; Rizkina, Tiara; Sastromihardjo, Andoyo (Polyglot, 2025)
This study aims to analyze syntactic errors in students' scientific articles, especially in the application of the principles of effective sentences. This study uses a qualitative descriptive approach with primary data in the form of 18 scientific articles in non-synta journals written by undergraduate or S-1 Indonesian Language and Literature study program students from 12 different universities as author affiliations. Data collection was carried out through documentation techniques, and analysis was carried out using a content analysis approach for three months, namely October to December 2024. The results of the study showed that the most common syntactic errors occurred in the aspects of unity of ideas, coherence, and emphasis. These errors include illogical combinations of ideas, lack of integration between sentences, and inability to emphasize the main idea. In addition, errors were also found in variations in sentence structure, parallelism, and logical reasoning. These findings reflect students' weak understanding of the basic principles of syntax and effective sentences. This study concludes that intensive training and guidance in academic writing are needed to improve the quality of students' scientific articles. These findings are expected to contribute to the development of scientific writing learning strategies in higher education.  Abstrak bahasa Indonesia  Penelitian ini bertujuan untuk menganalisis kesalahan sintaksis dalam artikel ilmiah mahasiswa, khususnya dalam penerapan prinsip kalimat efektif. Penelitian ini menggunakan pendekatan deskriptif kualitatif dengan data utama berupa 18 artikel ilmiah pada jurnal non sinta yang ditulis mahasiswa program studi Bahasa dan Sastra Indonesia jenjang sarjana atau S-1, dari 12 perguruan tinggi yang berbeda sebagai afiliasi penulis. Pengumpulan data dilakukan melalui teknik dokumentasi, dan analisis dilakukan dengan pendekatan analisis isi selama tiga bulan, yaitu bulan Oktober sampai dengan Desember 2024. Hasil penelitian menunjukkan bahwa kesalahan sintaksis paling umum terjadi pada aspek kesatuan gagasan, koherensi, dan penekanan. Kesalahan ini meliputi penggabungan ide yang tidak logis, kurangnya keterpaduan antar-kalimat, serta ketidakmampuan menekankan gagasan utama. Selain itu, ditemukan pula kesalahan dalam variasi struktur kalimat, paralelisme, dan penalaran logika. Temuan ini mencerminkan lemahnya pemahaman mahasiswa terhadap prinsip-prinsip dasar sintaksis dan kalimat efektif. Penelitian ini menyimpulkan bahwa pelatihan intensif dan bimbingan menulis akademik diperlukan untuk meningkatkan kualitas artikel ilmiah mahasiswa. Temuan ini diharapkan dapat memberikan kontribusi bagi pengembangan strategi pembelajaran menulis ilmiah di perguruan tinggi.